Dampak Content Marketing, Electronic Word Of Mouth Dan Brand Trust Pada Keputusan Pembelian Produk EBSCO - Abdullah; Sugiharti; Emi Wardati; Noor Salim; Nasnini (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2025)
Intense business competition highlights marketing strategy as a crucial factor for business sustainability and success. This phenomenon encourages business owners to optimize their marketing activities through e-commerce platforms. In the Indonesian market, various companies like Shopee, Tokopedia, and Lazada provide e-commerce facilities that are closely integrated with consumer shopping habits. This research aims to examine the extent of the influence of Content Marketing, Electronic Word of Mouth (E-WOM), and Brand Trust on Ebsco products marketed in Semarang City. To achieve this, 100 questionnaires were distributed to respondents in the Semarang City area. A non-probability sampling method was used for sample selection, with the Rao Purba formula being one of the approaches applied. The collected data were then processed and analyzed using SPSS software. The results of this study are: (1) Content Marketing has a positive and significant influence on purchasing decisions. (2) Conversely, Electronic Word of Mouth does not significantly influence purchasing decisions. (3) Similarly, Brand Trust also does not have a significant impact on purchasing decisions.